Organic matter in a water column of the Barents Sea. - Belyaeva, Alexandra N; Romankevich, Evgeny A (PANGAEA, 1982)
Concentration of dissolved and suspended organic carbon in the Barents Sea decreases with increasing depth and in meridional direction from south to north. This fact is attributed to uneven supply of organic matter (OM) from different sources. Large amounts of OM are present in the water column of the Barents Sea, which is a result of high productivity of this water mass and slow decomposition of OM at low temperatures and lowered activity of microflora. Larger amount of OM reaches bottom sediments of the Barents Sea more than in seas, which have similar depth and productivity, but are located at low latitudes. Characteristic features of distribution of lipids and suspended matter in sea water are examined.
Composition of organic matter in waters of the Barents Sea
Keywords: AK23-2010; AK23-2014; AK23-2028; AK23-2041; AK23-2042; AK23-2063; Akademik Kurchatov; AKU23; Archive of Ocean Data; ARCOD; Barents Sea; MULT